Keep these off the U.S.A. : buy more Liberty Bonds. - Norton, John Warner, 1876-1934 (artist):::Creator:::::::::::: (Cincinnati ; New York : The Strobridge Litho. Co.)
Bloodstained boots with the German imperial eagle insignia.